Fuzzy Logic Menganalisis Pengaruh Media Sosial Terhadap Perilaku Masyarakat Adat Kenagarian Kinari - Irzal Arief Wisky; Dhio Saputra (Ikatan Ahli Informatika Indonesia (IAII), 2018)
The purpose of this study was to build a Fuzzy Logic application to analyze the influence of social media on the behavior of the Kenagarian Kinari indigenous people. This research uses Fuzzy Logic Resistant model because in this method there is a variable in the form of frequency variables and activity variables on a fuzzy model, where later these variables can produce a fuzzy set as a benchmark, the higher the results of the fuzzy set obtained, the higher the effect on us, where the results are displayed in the form of community conditions related to the use of social media. The results of this study are also equipped with fuzzy membership degree representation and fuzzy processing conclusions that are displayed on information system applications using Visual Basic programming language, thus helping system users to analyze the influence of social media based on fuzzy variables, as well as the existence of Fuzzy Logic applications. social media influence on people's behavior. This system is capable of storing fuzzy set representations with 85% accuracy.